Efektivitas Pemberian Bacillus sp. D2.2 pada Media Teknis Molase terhadap Kualitas Air dan Performa Pertumbuhan Udang Vaname (Litopenaeus vannamei): The Effectivity of Bacillus sp. D2.2 in Molasses Technical Medium to Water Quality and Growth Performance of Vaname Prawns (Litopenaeus vannamei) - Ayu NOVITASARI; Ricky Nur ISKANDAR; Hefi Afizena ELVAZIA; Esti HARPENI; Tarsim TARSIM; Wardiyanto WARDIYANTO (Universitas Jambi, 2017)
Vanamei prawns have fast growth and can reared in high density. it has an impact on water quality deterioration and disruption of survival rates and growth. Various ways to cope has been done, one of them is with probiotic bacteria. The new strain of D2.2 bacteria is thought to be effective of ammonia utilization. Probiotics with local bacteria Bacillus sp. D2.2 is cultured on molasses technical medium to be applied semi-mass. The purpose of this study is to asses the efectivity of Bacillus sp. D2.2 inthe molasses technical medium on water quality and growth performance of vaname prawns (Litopenaeus vannamei). The research was used complete randomized design (RAL) with four treatments, A (Control), B (Application of 5 ppm Bacillus sp. D2.2 cultured in molasses technical medium), C (Application of 10 ppm Bacillus sp. D2.2 cultured in molasses technical medium), D (Application of 15 ppm Bacillus sp. D2.2 cultured in molasses technical medium) were repeated three times each. The results showed no effect on water quality and shrimp survival rate, but absolute growth (W), daily growth rate (GR) and feed conversion ratio (FCR) showed that B and C treatment had better than control. Keywords: Vaname shrimp, growth, Bacillus sp. D2.2, molasses technical medium